Flow em relacionamentos amorosos: mensuração e correlatos intraindividuais e psicossociais - Silva Neta, Olindina Fernandes da (2021)
Abstract: This thesis aims to verify the role of dark and virtuous personality traits, human values and love components on the flow experience in romantic relationships. Thus, the thesis was structured in three articles. Article 1, theoretical in nature, aims to present a brief background on the development of the Theory of Flow Experience proposed by Csikszentmihalyi (1997), its theoretical assumptions, measurement and correlates. In turn, Article 2 aimed to adapt to the Brazilian context a measure to measure flow in love relationships, the Flow State Scale (FSS). In Study 1, of an exploratory nature, 230 people participated (Mage = 30.27). Principal component analysis revealed a hexafactorial structure [focus (α = 0.83), perception of time (α = 0.77), loss of reflexive self-awareness (α = 0.76), fusion between action and consciousness (α = 0.57), autotelic experience (α = 0.76) and control of actions (α = 0.80)]. In study 2 (N = 249, Mage = 27.94) we sought to verify evidence of confirmatory factor validity, internal consistency and convergent validity. The results indicated that the hexafactorial model presented a significantly better fit when compared to the hierarchical and unifactorial models. The results of Cronbach's alpha, composite reliability and average variance extracted indicated that the components presented good levels of internal consistency, with the exception of the dimensions loss of reflexive self-awareness and fusion between action and awareness. Finally, it was found that the flow dimensions showed significant correlations with the well-being indicators. Article 3 aimed to understand the role of personality, human values and love components on flow in love relationships. Therefore, two studies were carried out. In Study 1, 249 people aged between 18 and 56 years participated, who answered the Flow Scale in Love Relationships, Dark Triad Dirty Dozen, Pro-Social Personality Inventory, Basic Values Questionnaire, in addition to sociodemographic questionnaires. The results indicated that narcissism was negatively correlated with loss of self-awareness. The virtuous personality traits correlated positively with the flow dimensions, especially the altruism and gratitude traits. Furthermore, the evaluative subfunctions were also positively correlated with the flow dimensions, especially interactive and experimentation. In Study 2, 201 people participated (M = 28.81, SD = 11.0). In addition to the Flow Scale in Love Relationships, participants responded to the Tetrangular Love Scale. In addition to the Flow Scale in Love Relationships, participants responded to the Tetrangular Love Scale. The results indicated a positive correlation between the components of love, within the scope of the Tetrangular Theory of Love, and the flow dimensions, highlighting the romantic passion component, which was an important predictor. Given the results, it is concluded that the Flow Scale in Love Relationships is psychometrically adequate and can be used to measure flow in love relationships in the Brazilian context. Furthermore, the role of intra-individual and psychosocial variables in the understanding of flow in romantic relationships was verified.